Closed-loop supply chain decision making and coordination considering channel power structure and information symmetry - Huo, Hong; Chen, Yuqiu; Wu, Rong (Frontiers in Energy Research, 2024)
China is currently undergoing a phase of high-quality development, with increasing emphasis on the circular economy, energy conservation, and environmental protection by both the government and enterprises. This paper examines a secondary supply chain comprising manufacturers and retailers, focusing on three supply chain decision-making models: one where the manufacturer is the channel leader, one where the retailer is the channel leader, and one where both parties have equal power. The study investigates the impact of manufacturers misrepresenting their Corporate Social Responsibility (CSR) information and the challenges associated with recycling efforts on the optimal performance of the supply chain. The findings reveal that when manufacturers lead the supply chain, they do not misrepresent their private information. However, when retailers dominate, manufacturers tend to underreport their CSR levels and the difficulty of recycling efforts. In scenarios where manufacturers and retailers have equal power, manufacturers do not misreport the difficulty of recycling but do underreport their CSR levels. This misreporting benefits the manufacturers at the expense of retailers and overall supply chain profitability, while also discouraging the recycling of used products. Across all three power structures, the study shows that retailers’ marketing efforts decrease as the misrepresentation of recycling difficulty increases, and increase as the misrepresentation of CSR levels increases. To mitigate the effects of manufacturers’ misreporting under information asymmetry, the paper proposes revenue-sharing contracts and two-part pricing contracts to coordinate the closed-loop supply chain under different power structures. Both contracts are shown to achieve Pareto improvements within the supply chain. This research provides valuable insights for enterprises operating within closed-loop supply chains, highlighting the importance of enhancing communication and cooperation to bridge information gaps and ensuring the coordina.